Psychographicnc and demographic profiles of credit card and non-cardholders in Urban Malaysia - Indar Kaur Dan Singh; Md. Nor Othman (Penerbit Universiti Kebangsaan Malaysia, 1995)
The study attempts to delineate the demographic and lifestyle characteristics of male credit card holders and non-holders in Malaysia. The two groups are compared using seven demographic and eight lifestyle variables. The results indicate that credit card holders tend to be slight~v older. married with children, have higher level of education and income, and are either professionals or work in a managerial capacity. The lifestyle profiles indicate that card holders tend to be low in their disbelief in credit, more self confident, socially active, risk oriented and less price conscious in their purchase behaviour.